2016
DOI: 10.1002/jctb.5079
|View full text |Cite
|
Sign up to set email alerts
|

Long-term operation of a pilot-scale reactor for phosphorus recovery as struvite from source-separated urine

Abstract: BACKGROUND: The treatment of source separated urine allows for a more sustainable approach to nutrients recovery in actual wastewater treatment plants. Struvite precipitation from urine yields a slow-release fertilizer (struvite) with a high marketable value for agricultural use. Extensive research on struvite precipitation has been carried out at laboratory scale, but there is still a lack of specific knowledge about the operation and key parameters at larger scale and over the long term. The effectiveness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 69 publications
1
30
0
Order By: Relevance
“…The recommended operating pH range is 8.5-9.5. With struvite precipitation, 85% of the P can be recovered while N can be recovered with a molar ratio 1:1 NH 4 to PO 4 or 0.46 N to P [74,75]. Struvite obtained from urine is a clean fertilizer, does not contain any OM, and has a negligible concentration of micropollutants and metals [76].…”
Section: Urine Treatmentmentioning
confidence: 99%
“…The recommended operating pH range is 8.5-9.5. With struvite precipitation, 85% of the P can be recovered while N can be recovered with a molar ratio 1:1 NH 4 to PO 4 or 0.46 N to P [74,75]. Struvite obtained from urine is a clean fertilizer, does not contain any OM, and has a negligible concentration of micropollutants and metals [76].…”
Section: Urine Treatmentmentioning
confidence: 99%
“…The saturation index (SI) was calculated according to Eqn (1): 27,28 where log IAP is the logarithm of the ion activity product calculated from the stoichiometry; Ks is the temperature-corrected thermodynamic solubility product; and SR is the supersaturation ratio. A SI greater than zero indicates that the solution is supersaturated, and a SI value 0 indicates the solution is in equilibrium or undersaturated.…”
Section: Calculations Of the Saturation Indexmentioning
confidence: 99%
“…A SI greater than zero indicates that the solution is supersaturated, and a SI value 0 indicates the solution is in equilibrium or undersaturated. 27 The SI at a fixed temperature of 25 ± 2 ∘ C was calculated based on Visual MINTEQ (ver. 3.1, Jon Petter Gustafsson, 2013).…”
Section: Calculations Of the Saturation Indexmentioning
confidence: 99%
“…It was therefore concluded that for an effective removal of N from wastewater through struvite precipitation, Mg:NH4:PO4 should be at least unity (Rahaman et al, 2011). In most cases, agricultural wastewater is deficient in Mg, and consequently Mg must be added (Zamora et al, 2017;Kataki et al, 2016). MgCl2 is preferred since this chloride salt has higher solubility compared to other magnesium compounds such MgO and Mg(OH)2 (Zamora et al, 2017;Kataki et al, 2016).…”
Section: Influence Of Molar Ratiomentioning
confidence: 99%